KONSEP PENDIDIKAN SUFISTIK ‘ABDUL WAHAB ASY-SYA’RÂNI - Subeidi Subeidi (Khatulistiwa, 2011)
This research on concept of Sufism by ‘Abdul Wahab asy-Sya’râni studies about the education components which covers: the aspects of purpose and teaching material, the aspects of teacher and students, the aspects of method and strategy in Sufism Education, as well as the relevance of Sufism education by asy-Sya’râni with the development of character building. The finding results of this research are: 1) The Sufism education by asy-Sya’râni is the one of which the main purpose is to reach ma'rifatullah. The levels of ma'rifatullah can be reached through syuhud, and reaching syuhud can be done by performing the study of universe, as already done by secular scientists. The difference is that the Syarâni’s Sufism education in performing the universe study needs spiritual condition; that is the pureness of soul which can be reached through the preaching materials such as żikr, tafakur, Qur’an recitation, istighfar and so on. Its implementation is that when the students learn the physics, biology and so on, they should do the prayer well and regularly. 2) Guru is the one guiding the students to direct to Allah by tracing His way. According to asy-Syarâni they are called mursyid. While the students are called sālik.Sālik is someone who spiriatually walks to be close to Allah to get His Blesssing. 3) The method in Sufism is called tarīqah. It is a path or way to reach man’ aim activities and efforts to increase the human personality by building and developing their potentiality.